2000
DOI: 10.1038/sj.bjp.0703557
|View full text |Cite
|
Sign up to set email alerts
|

Induction of COX‐2 and PGE2 biosynthesis by IL‐1β is mediated by PKC and mitogen‐activated protein kinases in murine astrocytes

Abstract: 1 Interleukin-1 (IL-1) is an important mediator of immunoin¯ammatory responses in the brain. In the present study, we examined whether prostaglandin E 2 (PGE 2 ) production after IL-1b stimulation is dependent upon activation of protein kinases in astroglial cells. 2 Astrocyte cultures stimulated with IL-1b or the phorbol ester, PMA signi®cantly increased PGE 2 secretion. The stimulatory action of IL-1b on PGE 2 production was totally abolished by NS-398, a speci®c inhibitor of cyclo-oxygenase-2 activity, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
129
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(147 citation statements)
references
References 59 publications
15
129
2
1
Order By: Relevance
“…these cultures (Figs 4-6) (see Parker et al 2002 for details). The activation of signaling pathways and subsequent release of inflammatory mediators in response to IL-1 has been described mainly in astrocytes (Molina-Holgado et al 2000). These observations suggest that responses of mixed glial cells to IL-1 are due mainly to activation of astrocytes via ligand binding to IL-1 receptors expressed on these cells (Fig.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…these cultures (Figs 4-6) (see Parker et al 2002 for details). The activation of signaling pathways and subsequent release of inflammatory mediators in response to IL-1 has been described mainly in astrocytes (Molina-Holgado et al 2000). These observations suggest that responses of mixed glial cells to IL-1 are due mainly to activation of astrocytes via ligand binding to IL-1 receptors expressed on these cells (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…These MAPKs are activated by IL-1 in glial cells Molina-Holgado et al 2000) and drive the transcription of genes for other inflammatory mediators such as IL-6 and prostaglandin-E 2 (PGE 2 ), resulting in their release.…”
mentioning
confidence: 99%
“…6D and 6E), indicating that PKC activation was important for IGF-I-mediated COX-2 transcriptional activation and mRNA stabilization. PKC was shown to regulate IL-1β-induced COX-2 expression through ERK1/2 activation in astrocytes (19). However, we found that pretreatment with the PKC inhibitor did not alter IGF-I-induced ERK1/2 activation in the cells (Fig.…”
Section: Pkc Activation Is Required For Igf-i-mediated Cox-2 Expressionmentioning
confidence: 69%
“…PKC activity regulated COX-2 expression induced by inflammatory stimuli and stress signals (16,19,47,49,50). Activation of PKC promotes COX-2 gene transcription through the transcription factors NF-κB and C/EBP (16,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation